THE MEANING OF THE CONCEPT OF “NAFS” IN ISLAMIC SOURCES - Norboyeva Surayyo Urazali qizi (International Multidisciplinary Journal for Research & Development, 2025)
One of the main topics of Sufism is the soul and its essence, and a number of studies are being carried out in world science. Psychological essence of Sufism as a religious phenomenon, stages of historical and gradual development, methodological problems of researching Sufism, issues of “spirit” (ruh), “soul” (nafs) and “psyche” related to the subject of Sufism psychology, problems of Sufism psychology as a science and solutions, self-awareness and improvement, spiritual education, cognitive psychological theory of Sufism, topical issues of Sufism in modern personality psychology, interpretation of Sufism’s concept of “I” in psychology, correlation between psychology and Sufism. This article analyzes the opinions of mystical scholars who expressed their views on the soul, its types and ways of educating it.